Cognitive prerequisites for fitness to drive: Norm values for the TMT, UFOV and NorSDSA tests. (2nd April 2020) - Selander, Helena; Wressle, Ewa; Samuelsson, Kersti
Abstract: Background: Fitness-to-drive assessment is a growing area for occupational therapists. There are few off-road tests specially developed to assess fitness to drive, and several cognitive tests have no age-specific norms. Aims/objectives: The aim was to identify and describe age-related norm values for the Trail Making Test, Nordic Stroke Driver Screening Assessment and Useful Field of View test, and to study inter-correlation between test results. Materials and methods: The sample included 410 volunteers; 149 men and 261 women, mean age 52 ± 16.8 years. Commonly used off-road tests were used: TMT A and B, UFOV and NorSDSA. Results: Normative data for the specific subtests and total score for NorSDSA and UFOV are provided and presented in four age groups. Age correlated with the results for most of the subtests. Conclusions: Off-road cognitive test scores are necessary and valuable for occupational therapists in their contribution to the final decision on continued driving. In clinical practice, it can be difficult to interpret cognitive test results when working with driving assessments. Age-based norm values are suggested to be a way to provide clinicians with a benchmark against which scores can be compared. Significance: Age-based norms can guide occupational therapists working with fitness to drive.